2003
DOI: 10.1074/jbc.m209486200
|View full text |Cite
|
Sign up to set email alerts
|

A Site in the Fourth Membrane-associated Domain of the N-Methyl-d-aspartate Receptor Regulates Desensitization and Ion Channel Gating

Abstract: The N-methyl-D-aspartate (NMDA) receptor has four membrane-associated domains, three of which are membrane-spanning (M1, M3, and M4) and one of which is a re-entrant pore loop (M2 The N-methyl-D-aspartate (NMDA) 1 receptor is a subtype of ionotropic glutamate receptor that plays essential roles in neuronal development, synaptic plasticity, and several types of neurological disorders (1). NMDA receptors are heteromers containing NR1 subunits, which bind the co-agonist glycine (2, 3), and NR2 subunits, which bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 50 publications
(56 reference statements)
6
74
2
Order By: Relevance
“…3 shows plots of power density spectra for NMDA-activated current in cells expressing NR1/ NR2A(M823I) and NR1/NR2A(M823L) mutant receptors. As we have observed previously (23) (14). In addition, a variance analysis of NMDAactivated current indicated that the unitary conductance of the ion channel was not changed in the presence of ethanol in receptors containing NR2A(M823I) or NR2A(M823L) mutant subunits (data not shown).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…3 shows plots of power density spectra for NMDA-activated current in cells expressing NR1/ NR2A(M823I) and NR1/NR2A(M823L) mutant receptors. As we have observed previously (23) (14). In addition, a variance analysis of NMDAactivated current indicated that the unitary conductance of the ion channel was not changed in the presence of ethanol in receptors containing NR2A(M823I) or NR2A(M823L) mutant subunits (data not shown).…”
Section: Resultssupporting
confidence: 79%
“…To test whether this site might participate in ethanol inhibition of NMDA receptors, we examined ethanol sensitivity of substitution mutants at this site. As we have reported previously, a number of amino acid substitutions at this site yielded nonfunctional receptors (23). All of the functional NR2A(Met 823 ) substitution mutant receptors tested were inhibited by ethanol in a concentration-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations